Electro-catalytic performance of 60%NiO/Ce0.9Zr0.1O2 cermets as anodes of intermediate temperature solid oxide fuel cells - Zimicz, Maria Genoveva (2013)
This paper analyses the electrocatalytic performance of a 60%NiO/Ce0.9Zr0.1O2 anode under reducing atmospheres, using a symmetric cell configuration, [anode/electrolyte/anode], with Samaria doped Ceria (SDC) as electrolyte. This anode exhibited excellent performance in H2 atmosphere in comparison with conventional anode materials. A dual chamber solid oxide fuel cell with 60%NiO/Ce0.9Zr0.1O2 anode, SDC electrolyte, and Pt cathode was constructed and tested under H2 atmospheres at intermediate temperatures. Good values of power densities were obtained, indicating the good performance of 60%NiO/Ce0.9Zr0.1O2 in the operating conditions.